PENERAPAN BUSINESS CONTINUITY MANAGEMENT PADA MASA PANDEMI COVID-19 DI PT BRANTAS ABIPRAYA - Tatan Sukwika; Wahyu Hery Sasongko (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2021)
Abripraya has implemented Business Continuity Management (BCM) as an effort to keep business processes running well under any risk conditions, including when the Covid-19 virus pandemic occurs. However, in Abipraya, there are still business risks that need to be resolved, namely violations of SOPs related to preventing Covid-19. This study aims to determine which risk groups are at high risk for applying Business Continuity Management in Abipraya during the Covid-19 pandemic. Data collection methods are used through field observations, documentation of activities, and interviews related to the object in the study. The results found six risks with a very high level, one chance with a high level, and a medium level due to violations of BCM implementation by Abipraya's external parties. The majority of breaches of the implementation of BCM by period-specific project workers such as vendors and subcontractors, visiting visitors, and online motorcycle taxi drivers. In conclusion, about 75% of the risk group with a very high-risk category for the BCM Abipraya during the Covid-19 pandemic. The managerial implication is to disseminate regulations, especially to external parties, and implement periodic mitigation plans to reduce high risk.